1971
DOI: 10.1103/physrevb.4.3321
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Band Calculation and the Optical Properties of Gold

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
151
0
2

Year Published

1973
1973
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(158 citation statements)
references
References 39 publications
5
151
0
2
Order By: Relevance
“…Thus, the interband onset energy shifts from about 2.3 eV in particles of lo4 atoms to 1.8 eV in particles of about 5 x lo2 atoms. In bulk gold the edge is due to direct transitions from Sd bands to the Ferrni level in the 6s band around L (threshold energy : 2.38 eV) with a small contribution of transitions near X (threshold : 1.7 eV) [46].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the interband onset energy shifts from about 2.3 eV in particles of lo4 atoms to 1.8 eV in particles of about 5 x lo2 atoms. In bulk gold the edge is due to direct transitions from Sd bands to the Ferrni level in the 6s band around L (threshold energy : 2.38 eV) with a small contribution of transitions near X (threshold : 1.7 eV) [46].…”
mentioning
confidence: 99%
“…Investigations [45] of the surface atoms on (110)-planes of A1 yielded changes of about 10 % compared to the volume. For bulk gold Christensen and Seraphin [46] computed the effects of lattice constant changes on band structure and dielectric constant. They found that the interband transitions at the threshold are shifted by-0.2 eV if the lattice is contracted by 2 %.…”
mentioning
confidence: 99%
“…3) Due to the absence of an interband transition contribution in Au beyond 600 nm [3]. Figure 9 shows the size dependent relaxation time 1ï/1:e for Au versus the particle radius.…”
Section: Dielectric Functions Ofmentioning
confidence: 99%
“…Regarding the electronic structure Au [3] and Pt [4] The D.C. resistivity of the films was deduced from resistance measurements using an electrometer (before percolation) or a resistance bridge (near and after percolation).…”
mentioning
confidence: 99%
“…Due to its well-known optical properties, 19,24 gold has been the metal most widely studied in optical pump-probe measurements. A correct understanding of its transient reflectivity provides a basis for the understanding and quantification of experiments on other metals.…”
Section: Introductionmentioning
confidence: 99%